2003
DOI: 10.1191/0961203303lu319oa
|View full text |Cite
|
Sign up to set email alerts
|

Quinacrine added to ongoing therapeutic regimens attenuates anticardiolipin antibody production in SLE

Abstract: The benefit of combining quinacrine (Qn) with hydroxychloroquine (HCQ) in the treatment of systemic lupus erythematosus (SLE) was previously re-evaluated by us. In our current study we observed that, in 11 active SLE patients (SLEDAI score 5-12), the addition of Qn (100 mg/day) to their existing ongoing therapeutic regimens resulted in a significant attenuation of their previously persistent anticardiolipin antibody (aCL) response. This was in comparison with a matched non-Qn treated control group composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In our previous study, we have shown that add-on Qn decreased SLEDAI scores and was of steroid sparing effect in SLE [12]. In a further study, we were also able to show that Qn treatment attenuated long-lasting aCL titres in SLE patients [24]. The reduction effect of this regimen on both serum BAFF and aCL should encourage more frequent usage of Qn in the treatment of SLE patients.…”
Section: Discussionmentioning
confidence: 54%
“…In our previous study, we have shown that add-on Qn decreased SLEDAI scores and was of steroid sparing effect in SLE [12]. In a further study, we were also able to show that Qn treatment attenuated long-lasting aCL titres in SLE patients [24]. The reduction effect of this regimen on both serum BAFF and aCL should encourage more frequent usage of Qn in the treatment of SLE patients.…”
Section: Discussionmentioning
confidence: 54%
“…In the Baltimore Lupus Cohort, hydroxychloroquine use was found to be protective in reducing the risk for future thrombus; however, it was not clear if hydroxychoroquine was a primar y factor [40]. In a recent clinical trial, addition of quinacrine to SLE aCL-positive patients being treated with hydroxychloroquine resulted in disappearance of the aCL in eight of 11 study subjects (P = 0.004) compared with only three in 14 nonquinacrine treated controls (P = 0.18) [42]. There have been safety concerns about the use of hydroxycholoquine in pregnancy; however, a recent review of hydroxychloroquine use in pregnancy did not find any increase in the rate of birth defects in more than 250 pregnancies in which hydroxychloroquine was used for an underlying connective tissue disease [43].…”
Section: Antimalarial Drugsmentioning
confidence: 98%
“…This agent also appears to decrease aCL levels in humans [Toubi et al 2003]. No teratogenicity has been described with the use of hydroxychloroquine in pregnant women with SLE [Motta et al 2005;Khamashta et al1996;Parke and West, 1996]; however, the safety and efficacy of this drug in pregnant women with APS have not been examined in large clinical trials.…”
Section: Management Of Pregnancymentioning
confidence: 99%